2022
DOI: 10.3390/en15124350
|View full text |Cite
|
Sign up to set email alerts
|

Physics-Based Proxy Modeling of CO2 Sequestration in Deep Saline Aquifers

Abstract: The geological sequestration of CO2 in deep saline aquifers is one of the most effective strategies to reduce greenhouse emissions from the stationary point sources of CO2. However, it is a complex task to quantify the storage capacity of an aquifer as it is a function of various geological characteristics and operational decisions. This study applies physics-based proxy modeling by using multiple machine learning (ML) models to predict the CO2 trapping scenarios in a deep saline aquifer. A compositional reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 66 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…Following (iii to x) are the chemical reactions after interaction of Sc-CO 2 -water-rock minerals, which causes mineral dissolution and new mineral precipitation by altering the pore structure ,, CO 2 + H 2 O H + + HCO 3 2 H + + CO 3 2 …”
Section: Interaction Of Sc-co2 With Shalementioning
confidence: 99%
“…Following (iii to x) are the chemical reactions after interaction of Sc-CO 2 -water-rock minerals, which causes mineral dissolution and new mineral precipitation by altering the pore structure ,, CO 2 + H 2 O H + + HCO 3 2 H + + CO 3 2 …”
Section: Interaction Of Sc-co2 With Shalementioning
confidence: 99%
“…A particular focus is on understanding the reactions involving carbonate minerals and the crucial parameters that govern these reactions. This study uses a stochastic approach to model the kinetic parameters, which is different from other studies conducted in the literature, which either model the geochemical reactions deterministically [11,25,26] or neglect them altogether [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the saltier formation water is, the less solubility trapping happens as water has the limited potential to dissolve ions and chemical substances. A Khanal and Shahriar 34 investigated CO 2 trapping in a deep saline aquifer using an artificial neural network. It was observed that over time, the effect of the residual trapping decreased, while the effect of the solubility mechanism gradually increased.…”
Section: Introductionmentioning
confidence: 99%